2020
DOI: 10.3390/ijms21031084
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol Alleviates Gamma Irradiation-Induced Damage by Modulating Diverse Inflammatory Mediators

Abstract: The present study aimed to explore the possible radioprotective effects of celastrol and relevant molecular mechanisms in an in vitro cell and in vivo mouse models exposed to gamma radiation. Human keratinocytes (HaCaT) and foreskin fibroblast (BJ) cells were exposed to gamma radiation of 20 Gy, followed by treatment with celastrol for 24 h. Cell viability, reactive oxygen species (ROS), nitric oxide (NO) and glutathione (GSH) production, lipid peroxidation, DNA damage, inflammatory cytokine levels, and NF-κB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 90 publications
0
12
0
Order By: Relevance
“…This suggestion is due to the presence of beneficial natural chemicals in plants and fruits and, also, their metabolites, which exert health-promoting effects after being absorbed in the body [3][4][5][6][7][8][9][10]. It has been demonstrated that the identification, isolation, and purification of these natural chemicals may be a milestone in the treatment of diseases, particularly in human malignancies [11][12][13][14][15][16][17][18][19][20]. A high number of studies have focused on cancer therapy using plant-derived natural compounds [6,[13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…This suggestion is due to the presence of beneficial natural chemicals in plants and fruits and, also, their metabolites, which exert health-promoting effects after being absorbed in the body [3][4][5][6][7][8][9][10]. It has been demonstrated that the identification, isolation, and purification of these natural chemicals may be a milestone in the treatment of diseases, particularly in human malignancies [11][12][13][14][15][16][17][18][19][20]. A high number of studies have focused on cancer therapy using plant-derived natural compounds [6,[13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…This triterpene also dampens HIV-1 Tat-induced inflammatory responses, inhibits the production of proinflammatory chemokines, such as CXCL10, IL-8, and MCP-1 (YOUN et al, 2014), and suppresses replication of Dengue virus serotype 1-4 by promoting IFN-α expression and stimulating downstream antiviral responses 74 . Celastrol suppresses the production of cytokines during cytokine storm and of chemokines related to worse disease prognosis, such as IL-8, IL-6, CXCL1, and CCL20 [75][76][77] , lowers the levels of anti-inflammatory markers 78 , and stimulates type I interferon production and expression of interferon-stimulated genes against Dengue virus infection 74 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study using a mouse model of acute toxicity has demonstrated that celastrol is safe even when orally administered at a high dose (62.5 mg/kg body weight) 110 . Intraperitoneal administration of celastrol (0.25 mg/kg body weight) increases the gamma irradiated-mice survival rate by around 70 78 . To surpass celastrol toxicity, solubility, and pharmacokinetic issues, several pharmaceutical approaches have been proposed, such as nanoencapsulation, liposomes, and sugar-silica nanoparticles [111][112][113] .…”
Section: Discussionmentioning
confidence: 99%
“…The four compounds that suppress wRiinduced CI are known inducers of DNA damage, whereas the three compounds that suppress both wRi-and wMel-induced CI, reportedly support DNA integrity ( Figure 5) (Additional File S3). Though celastrol can exert detrimental impacts on DNA (Han et al, 2018;Wang et al, 2020), it has also been shown to suppress radiation-induced damage (Xu et al, 2013;Moreira et al, 2019). Cycloheximide treatments prevent formation of single-and double-strand DNA breaks (Yoshioka et al, 1987;Lorico et al, 1988).…”
Section: Discussionmentioning
confidence: 99%